1997
DOI: 10.1016/s0009-9236(97)90027-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of intestinal P-glycoprotein (mdr1) in interpatient variation in the oral bioavailability of cyclosporine*

Abstract: Interpatient differences in the oral clearance of cyclosporine (INN, ciclosporin) have been partially attributed to variation in the activity of a single liver enzyme termed CYP3A4. Recently it has been shown that small bowel also contains CYP3A4, as well as P-glycoprotein, a protein able to transport cyclosporine. To assess the importance of these intestinal proteins, the oral pharmacokinetics of cyclosporine were measured in 25 kidney transplant recipients who each had their liver CYP3A4 activity quantitated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
402
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 642 publications
(422 citation statements)
references
References 40 publications
16
402
0
4
Order By: Relevance
“…Broad substrate specificity of P-gp is a major factor responsible for subtherapeutic levels of various drugs in blood and tissues (Varma et al, 2003). A recent report suggests that presence of this efflux transporter on the brush border membrane of intestinal epithelium not only diminishes permeability of various therapeutic agents but also enhances the metabolism of these molecules by effluxing the drugs into the intestinal lumen or blood capillaries thereby increasing drug exposure to cellular as well as lumenal enzymes (Lown et al, 1997;Watkins, 1997;Ito et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Broad substrate specificity of P-gp is a major factor responsible for subtherapeutic levels of various drugs in blood and tissues (Varma et al, 2003). A recent report suggests that presence of this efflux transporter on the brush border membrane of intestinal epithelium not only diminishes permeability of various therapeutic agents but also enhances the metabolism of these molecules by effluxing the drugs into the intestinal lumen or blood capillaries thereby increasing drug exposure to cellular as well as lumenal enzymes (Lown et al, 1997;Watkins, 1997;Ito et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Broad substrate specificity of P-gp is a major factor responsible for sub-therapeutic levels of various drugs in blood and tissues (Varma et al, 2003). Recent reports suggest that the presence of this efflux pump on the brush border membrane of intestinal epithelium not only diminishes permeability of various therapeutic agents but also enhances the metabolism of these molecules by effluxing the drug into the intestinal lumen or blood capillaries thereby increasing the drug exposure to cellular as well as luminal enzymes (Lown et al, 1997;Watkins, 1997;Ito et al, 1999). Several strategies have been employed to bypass or inhibit this efflux transporter and increase the oral bioavailability of such therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that P-glycoprotein (P-gp) and/or CYP3A limit the oral bioavailability of digoxin, rifampin [4], vinblastine [5], dexamethasone tromethorphan [6], tacrolimus [7], sirolimus [8] and cyclosporin A [9,10]. Lown et al [11] suggested that P-glycoprotein…”
Section: Introductionmentioning
confidence: 99%